1996
DOI: 10.1074/jbc.271.30.17779
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation of Fibroblast Collagen and Transforming Growth Factor β1 Gene Expression by Monocyte Chemoattractant Protein-1 via Specific Receptors

Abstract: Recent studies indicate potential roles of monocyte chemotactic protein-1 (MCP-1) in recruitment of monocytes to sites of inflammation. However, their increased expression does not always correlate with monocyte influx, suggesting other possible biological activities for this member of the C-C chemokine family. In view of its potential role in regulating extracellular matrix expression in fibrotic disorders, the effects of MCP-1 on lung fibroblast collagen expression were evaluated. Isolated rat lung fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
290
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(307 citation statements)
references
References 44 publications
14
290
1
2
Order By: Relevance
“…Exposure to MCP-1 induced a statistically significant 2.5-fold increase in fibronectin protein levels at 24 h, which was comparable with the increase in extracellular matrix induced by MCP-1 in rat lung fibroblasts [31]. The rise in fibronectin protein levels in the supernatant fraction was followed by a significant increase in pericellular polymeric fibronectin, indicating enhanced fibronectin incorporation in the matrix.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Exposure to MCP-1 induced a statistically significant 2.5-fold increase in fibronectin protein levels at 24 h, which was comparable with the increase in extracellular matrix induced by MCP-1 in rat lung fibroblasts [31]. The rise in fibronectin protein levels in the supernatant fraction was followed by a significant increase in pericellular polymeric fibronectin, indicating enhanced fibronectin incorporation in the matrix.…”
Section: Discussionsupporting
confidence: 62%
“…SB202190 and the rabbit anti-fibronectin antibody were from Calbiochem (Nottingham, UK). The protein kinase C (PKC) peptide inhibitors PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and SN50 were from Alexis (Nottingham, UK) and the TransAM nuclear factor kappa B (NF-κB) kit was from Active Motif (Rixensart, Belgium). The FITC-conjugated rabbit antimouse antibody, the rabbit anti-fibronectin antibody and the avidin/biotin blocking solution were from DAKOCytomation (Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, both CXCL8 and CCL2 concentrations were found to be increased in blood (Ziegenhagen et al, 1998a;Suga et al, 1999;Fujiwara et al, 2012) and bronchoalveolar lavage fluid (BALF) (Capelli et al, 2005;Antoniou et al, 2006;Baran et al, 2007) of IPF patients compared with healthy volunteers and correlated with lung function (Capelli et al, 2005;Emad and Emad, 2007;Martina et al, 2009;Vasakova et al, 2009), disease progression (Ziegenhagen et al, 1998b;Totani et al, 2002), and outcome (Shinoda et al, 2009;Richards et al, 2012). Furthermore, several studies suggested an involvement of the chemokine CCL2 in the pathogenesis of IPF, notably through its action on resident pulmonary fibroblast and circulating fibrocytes, promoting the generation of abundant extracellular matrix in the lungs (Gharaee-Kermani et al, 1996;Phillips et al, 2004;Moore et al, 2005;Inomata et al, 2014). Such strong evidence involving CXCL8 in the pathogenesis of the disease are lacking, although this chemokine is thought to act as a pro-fibrotic factor in IPF via the promotion of exacerbated angiogenesis (Strieter et al, 2002;Rosenkilde and Schwartz, 2004;Antoniou et al, 2006;Martina et al, 2009;Cui et al, 2010).…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%